Bergamot and Olive Extracts as Beer Ingredients: Impact on Cell Viability, Reactive Oxygen Species, and RNA Expression of Antioxidant Enzymes - Maria Laura Matrella; Bruna Amenta; Francesco Canino; Angela Maffia; Tiziana Cocco; Mariateresa Russo; Adele Muscolo (Foods)
This study explores the incorporation of bergamot juice and olive extract as functional ingredients in craft beer and their effects on antioxidant activity and cellular oxidative stress. Lyophilized beer samples were applied to human fibroblast cells at concentrations of 0.31 and 0.62 µg/µL for 24 and 48 h. Cell viability, reactive oxygen species (ROS) levels, and antioxidant gene expression were evaluated. Beers enriched with bergamot (Heraclea) and olive extract (Elais) significantly reduced ROS levels compared to base beers (Blanche and Weiss), particularly at lower concentrations and shorter exposure times. However, prolonged treatment showed variable effects, suggesting possible concentration- and time-dependent pro-oxidant behavior. Gene expression analysis revealed the upregulation of the antioxidant enzyme SOD2 in all samples except Elais under oxidative stress, indicating differential cellular responses. These findings suggest that functional beers enriched with plant extracts may offer antioxidant benefits and support cellular defense mechanisms, representing a promising direction in wellness-oriented brewing.